PERIODIZATION OF POLITICAL AND ADMINISTRATIVE REFORMATION OF PUBLIC ADMINISTRATION MANAGEMENT SYSTEM IN UKRAINE - U.A. Sack (Theory and Practice of Public Administration, 2019)
The purpose of the study is a systematic analysis of the periods of implementation of political and administrative reform of the public administration system in Ukraine and the formation of ways for further reforms.The first stage of the reform began with the adoption of the Presidential Decree "On the State Commission for the Administration Reform in Ukraine". The Concept envisaged a significant increase in the status of the government, increase of its authority and strengthening of positions with regard to the President of Ukraine and the Verkhovna Rada of Ukraine, a significant strengthening of the role of ministries in the formation of state policy, clear allocation and differentiation of the status, powers and functions of various groups of executive authorities, the influence of the government and the central executive authority on the local level of executive power, improvement of administrative procedures, etc.The second stage - the stage of reforming the higher and central levels of the system of executive power was associated with the new course of the state for accession to the EU, set out in the Strategy for Economic and Social Development for 2000-2004.The third stage of reforming includes changes due to the adoption of the Law of Ukraine "On amendments to the Constitution of Ukraine", preparation of administrative and territorial reform, local self-government reform, public service reform (civil service and service in local self-government bodies), as well as preparation of a new Concept of administrative Reforms (Concept of Reforming Public Administration).IV stage of reformation began in 2010 with the advent of the program documents of the President of Ukraine and the Government of Ukraine. During this period, theoretical and methodological principles of administrative reform, in particular its categorical-conceptual apparatus, are being modernized.V stage of reforming - 2011-2013 - adoption of the long-awaited Law of Ukraine "On Central Executive Bodies", which for the first time in the history of Ukrainian independence at the level of the law has defined the types of central executive bodies, their system and competence.VІ stage of the reforming of 2014 - the beginning of a new stage of political and administrative reform, connected with the introduction of amendments to the Constitution of Ukraine by adopting the Law of Ukraine "On Restoring the Effects of Certain Provisions of the Constitution of Ukraine" and bringing in the Law of the State of the entire legal and regulatory framework in accordance with the Basic Law, first of all those laws and by-laws concerning the organization of the system of executive bodies, the Law of Ukraine "On the Cabinet of Ministers of Ukraine", the introduction of amendments to the Law of Ukraine "On Central Executive Bodies and ", the introduction of amendments to the Law of Ukraine" On Local State Administrations ", etc.To date, the fifth stage of reforming the system of public administration begins. Thus, the Decree of the President of Ukraine provides for the formation of the Office of the President of Ukraine through reorganization and reduction of the number of employees of the Administration of the President of Ukraine.